1999
DOI: 10.2527/1999.77113007x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy density and lysine:calorie ratio on growth performance and carcass characteristics of growing-finishing pigs.

Abstract: We conducted two experiments to evaluate the effects of dietary energy density and lysine:calorie ratio on the growth performance and carcass characteristics of growing and finishing pigs. In Exp. 1, 80 crossbred barrows (initially 44.5 kg) were fed a control diet or diets containing 1.5, 3.0, 4.5, or 6.0% choice white grease (CWG). All diets contained 3.2 and 2.47 g of lysine/Mcal ME during growing (44.5 to 73 kg) and finishing (73 to 104 kg), respectively. Increasing energy density did not affect overall ADG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
51
3
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 25 publications
11
51
3
6
Order By: Relevance
“…Added dietary fat has been shown to improve HCW and carcass yield (Smith et al, 1999;Jackson et al, 2009), whereas others have shown no affect, which would agree with findings from the present study (Bee et al, 2002; 2 C22:6n3 not included; all values were equal to or less than 0.003.…”
Section: Discussionsupporting
confidence: 82%
“…Added dietary fat has been shown to improve HCW and carcass yield (Smith et al, 1999;Jackson et al, 2009), whereas others have shown no affect, which would agree with findings from the present study (Bee et al, 2002; 2 C22:6n3 not included; all values were equal to or less than 0.003.…”
Section: Discussionsupporting
confidence: 82%
“…These results confirm those obtained by LopezBote et al (1997), Smith et al (1999) and Stein et al (1996), who have all observed an increase in carcass yield when assessing different levels of ME while maintaining the lysine:energy ratio for growing and finishing pigs.…”
Section: Resultssupporting
confidence: 82%
“…As is also assumed in other pig growth models (Whittemore et al, 2001;van Milgen et al, 2008), the modified InraPorc model used in this study assumed that pigs do not modify feed intake during or after lysine-deficient periods. The assumption that pigs do not increase feed intake to meet their requirements when fed lysine-deficient diets is supported by some authors (Owen et al, 1994;Nam and Aherne, 1994) but not by others (Smith et al, 1999;Cline et al, 2000). Feeding pigs at levels below Lys requirements limits protein growth and pigs become fatter and lighter.…”
Section: Resultsmentioning
confidence: 99%